Matharpacady-01.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Matharpacady is a historic village (or gaothan in the local language) in Mazagaon, wedged between R. Naik Road and Champsi Bhimji Road. The Gaothan was settled by the East Indian community more than two centuries ago, or possibly even earlier. Over time, due to the original East Indians migrating to other parts of Mumbai and emigration to foreign countries, various other communities have moved in and made Matharpacady their home.